Description of a new species of the genus Dendrothrips Uzel (Thysanoptera: Thripidae) from Japan - Noguchi, Soichiro; Masumoto, Masami (Zootaxa, 2019)
A new species, Dendrothrips kinape, is described and illustrated from Oryza sativa at Hokkaidô, Japan. In this genus, this species is very peculiar in its uniformly pale body color and in its host plant (first record from Monocotyledoneae). A key to Japanese species of the genus is provided.